La población ocupada y el empleo informal en el Perú durante el periodo 2017 - 2021 - Flores Vela, César Neyzer (2023)
The employed population in Peru is made up of workers who work in the formal and informal sectors, the latter being the most difficult to control. The employed population is measured through the Economically Active Employed Population (EAP Employed). The objective proposed in the research is to determine the relationship between the employed population and informal employment in Peru during the period 2017 - 2021. For this purpose, the research is carried out, which is of a Quantitative type, of a Correlational level and of a Non-Experimental design. The conclusions are: the employed population is directly associated with informal employment, a statement that arises as a product of the application of the statistical test, with the Correlation Coefficient of r = 0.883487678; and the Coefficient of Determination R2 = 0.780550478. In this same sense, it is observed that 50.50% of the employed population has been working Adequately Employed, while 49.50% does so as Underemployed. Informal employment has Independent Worker as its main occupation category, concentrating 45.46% of informal workers, which is equivalent to the average number of 5,543,600 people, followed by the category Workers, which is equal to 22.22% of the total. In this same sense, the analysis of informal employment according to the size of the company shows that the From 01 to 10 People congregate 89.56% of the workers in the sector.